Cave Excavations in East Fife: With Descriptions of the Animal Remains (Proceedings of the Society of Antiquaries of Scotland, 1915)
The Kinkell Cave near St Andrew's was occupied during the Roman and early Christian periods. Artefacts included boar tusks, many shells, pottery and a slab incised with a human figure and a number of crosses. Constantine's Cave near Fife Ness was occupied at the same time with a comparable range of artefacts, although the whole front of the cave was walled. Crosses and animal figures were incised on the cave wall.